Impacts of Various Reheating Methods on Crispy Chicken: Physicochemical Properties, Oxidation and Flavor Profiles - Xiaona Ren; Chun Wang; Xueqing Wang; Tingting Su; Yigang Yu (Foods)
In this study, the impacts of water-bath reheating (WR), steam reheating (SR), air-frying reheating (AR), roasting reheating (RR), and microwave reheating (MR) on the physicochemical properties, oxidation, and flavor profiles of crispy chicken (CC) were investigated. The results revealed that the pH of CC was significantly reduced after reheating (p < 0.05). The AR samples had a slight change in L* and the highest springiness. The RR samples had the highest degree of lipid and protein oxidation. In addition, WR, AR, RR, and MR treatments effectively increased the contents of umami-related amino acids. Glu and Cys were typically the taste-active amino acids in CC. AR contributed to increasing the response values of umami and richness. As shown by the electronic nose and Gas Chromatography–Mass Spectrometry (GC-MS) analysis, 41 volatile compounds were obtained in CC. AR could efficiently increase the contents of nitrogen oxides and methyl compounds. Meanwhile, the content of trans-.alpha.-bergamotene, nonanal, and copaene were significantly increased after the AR process (p < 0.05). According to the results of analysis of variance (ANOVA), odor activity value (OAV), and variable importance in projection (VIP), anethole was considered the key differential flavor-active compound. Overall, AR was superior to other reheating methods in CC, with better texture and various flavor characteristics. This study provides a reference for choosing reheating technology for pre-cooked chicken products.